Financial Performance Analysis Based on the Balance Scorecard Method in Makassar City Regional Drinking Water Company (PDAM) - Nurhasika Nurhasika; Syamsul Alam; Fauzi R Rahim (CV. Ulil Albab Corp, 2023)
This research aims to determine financial performance based on the balance scorecard in PDAM Makassar City. The results of this research show that overall, the company's performance seen from 4 (four) Balanced Scorecard perspectives can be said to be good because the company was able to achieve 75% of the standards set or as many as six of the eight benchmarks used by the balanced scorecard succeeded in meeting the target.